Time course of blood pressure and vascular adaptations to intermittent hypobaric hypoxic exercise - Ogita, F.; Kurobe, K.; Huang, Z.; Nagira, A.; Nishiwaki, M.; Tanaka, T.; Tamaki, H. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Recently, we have observed that aerobic exercise in hypobaric hypoxia of 4 weeks could induce beneficial circulatory adaptations, such as a reduction of total peripheral resistance and blood pressure, and an increase in flow mediated vasodilation (FMD) response, stroke volume, and cardiac output (Ogita 2008). However, time course of such cardiovascular adaptations have not been clarified. Therefore, the present study evaluated the time course of blood pressure and vascular adaptations to intermittent hypobaric hypoxic exercise. Methods: Twelve healthy male adults (22±1 yrs) were matched for physical fitness level into two groups, and then randomized to normobaric normoxic exercise group (N, n=6) and hypobaric hypoxic exercise group (H, n=6). The subjects had aquatic exercise training in swimming pool located in a chamber where atmospheric pressure could be regulated. The exercise was performed at the intensity of around 50%VO2max for 30 minutes/training session, 4 days/week, for 4 weeks. H had the exercise in hypobaric hypoxia corresponded to 2000m above sea level, and was exposed to the condition for 2 hours/session. Before and after the training, systolic (SBP), diastolic (DBP), and mean blood pressure (MBP) were determined at rest and during cycling exercise at 50%VO2max, which was determined before the training. Also, arterial stiffness was assessed by cardio ankle vascular index (CAVI), and FMD was evaluated by peak diameter of the popliteal artery during reactive hyperemia, which was measured by ultrasound imaging system. Results: After the 4 weeks of training, no significant changes were observed in most valuables in N through the training period. On the other hand, a significant decrease in SBP and MBP during moderate exercise was found within one week in H (P<0.05). A significant decrease in arterial stiffness assessed by CAVI was also observed within 2 weeks (P<0.05), whereas no significant changes were observed in %FMD through the training period. Discussion: Our findings suggest that intermittent hypobaric hypoxic exercise could bring beneficial vascular adaptations within 1-2 weeks, such as a significant reduction of blood pressure associated with a decrease in arterial stiffness.